2023
DOI: 10.1007/s42452-023-05341-8
|View full text |Cite
|
Sign up to set email alerts
|

Novel and flexible asymmetric supercapacitors based on NiCo2O4 nanosheets coated on Al and Cu tapes for wearable devices applications

Abstract: The binary metal oxides show advantages in energy storage devices. Specifically, nickel cobaltite (NiCo2O4) materials showed promising pseudocapacitive properties, high electrical conductivity and large surface area by virtue of their effective porous structure. NiCo2O4 nanosheets were hydrothermally grown in this work over flexible tapes of Aluminum (Al) and Copper (Cu). A nanosheets structure obtained of NiCo2O4 as confirmed by SEM and AFM images. The measured thickness by 3D profilometer of NiCo2O4 nanoshee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…It is known that the functional characteristics of materials are determined not only by their chemical composition and dispersity but also by their microstructure. A number of papers [ 25 , 26 , 27 , 28 , 29 , 30 ] have demonstrated that obtaining hierarchically organized nanostructures, including those consisting of anisotropic particles, when creating materials for modern energy storage devices allows the length of the charge (ion/electron) transfer path to be reduced, the active surface area to be increased, and the bulk density of the resulting electrode materials to be decreased. This, in turn, contributes to increasing electrochemical activity and capacitance of electrodes, improving their microstructural stability during cyclic charging–discharging.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the functional characteristics of materials are determined not only by their chemical composition and dispersity but also by their microstructure. A number of papers [ 25 , 26 , 27 , 28 , 29 , 30 ] have demonstrated that obtaining hierarchically organized nanostructures, including those consisting of anisotropic particles, when creating materials for modern energy storage devices allows the length of the charge (ion/electron) transfer path to be reduced, the active surface area to be increased, and the bulk density of the resulting electrode materials to be decreased. This, in turn, contributes to increasing electrochemical activity and capacitance of electrodes, improving their microstructural stability during cyclic charging–discharging.…”
Section: Introductionmentioning
confidence: 99%